Analisis Peranan Kompensasi Dalam Meningkatkan Kinerja Karyawan di Kantor Lembaga Zakat Washliyah Beramal - Muhammad Arif; Siswardi Brasa (LPPM IAI Nasional Laa Roiba Bogor, 2022)
This study aims to describe and reveal how the role of compensation in the charity wasliyah zakat institution (LAZ WASHAL) can improve the performance of employees in this office. This research was conducted using qualitative research with descriptive methods. Compensation is anything that employees receive in return for their work. Compensation is also one of the most effective ways for the personnel department to improve employee performance, motivation and job satisfaction. A good compensation system will be able to provide satisfaction for employees and allow companies to acquire, hire, and retain employees. The existence of compensation at the charity wasliyah zakat institution has a positive impact and becomes one of the benchmarks for improving employee performance. Keywords: Role of Compensation, Compensation, Employee Performance